Competence-based Vocational and Professional Education [electronic resource] : Bridging the Worlds of Work and Education - Mulder, Martin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a comprehensive overview of extant literature on competence-based vocational and professional education since the introduction of the competence concept in the 1950s. To structure the fi eld, the book distinguishes between three approaches to defi ning competence, based on 1.functional behaviourism, 2. integrated occupationalism, and 3. situated professionalism. It also distinguishes between two ways of operationalizing competence: 1. behaviour-oriented generic, and 2. task-oriented specifi c competence. Lastly, it identifi es three kinds of competencies, related to: 1. specific activities, 2. known jobs, and 3. the unknown future. Competence for the unknown future must receive more attention, as our world is rapidly evolving and there are many ?glocal? challenges which call for innovation and a profound transformation of policies and practices. Th e book presents a range of diff erent approaches to competence-based education, and demonstrates that competencebased education is a worldwide innovation, which is institutionalized in various ways. It presents the major theories and policies, specifi c components of educational systems, such as recognition, accreditation, modelling and assessment, and developments in discipline-oriented and transversal competence domains. Th e book concludes by synthesizing the diff erent perspectives with the intention to contribute to further improving vocational and professional education policy and practice. Joao Santos, Deputy Head of Unit C5, Vocational Training and Adult Education, Directorate General for Employment, Social Aff airs and Inclusion, European Commission: ?This comprehensive work on competence-based education led by Martin Mulder, provides an excellent and timely contribution to the current debate on a New Skills Agenda for Europe, and the challenge of bridging the employment and education and training worlds closer together. Th is book will infl uence our work aimed at improving the relevance of vocational education to support initial and continuing vocational education and training policy and practice aimed at strengthening the key competencies for the 21st century.? Prof. Dr. Reinhold Weiss, Deputy President and Head of the Research, Federal Institute for Vocational Education and Training (BIBB), Bonn, Germany: ?This book illustrates that the idea and concept of competence is not only a buzzword in educational debates but key to innovative pedagogical thinking as well as educational practice.? Prof. Dr. Johanna Lasonen, College of Education, University of South Florida, Tampa, USA:'Competence-based Vocational and Professional Education is one of the most important multi-disciplinary book in education and training. Th is path-breaking book off ers a timely, rich and global perspective on the fi eld. Th e book is a good resource for practitioners, policymakers and researchers.'.
Introduction -- 1 Introduction -- Part I Theory: Conceptual Foundations, Concerns and Perspectives -- 2 Developing domains of occupational competence: Workplaces and learner agency -- 3 Competence, qualification and action theory -- 4 Competence and professional expertise -- 5 Competence, capabilities and graduate attributes -- 6 Using an epistemological perspective to understand competence-based vocational and professional education -- 7 Mindful Working and Skilful Means: Enhancing the affective elements of vocational education and training through the ethical foundations of mindfulness -- 8 Competence- based education and teacher professional development -- 9 Beyond competence, thinking through the changes: Economy, work and neo-Liberalism -- 10 The integrated view on competence -- 11 Competence and the alignment of education and work. Part II Competence-based Education as a Global Innovation -- II.I The USA: Where it all began -- 12 Competence-based education in the USA -- 13 Competence-based education and assessment in the accounting profession in Canada and the United States -- II.II Diverse European Approaches -- 14 NVQs and approaches to competence in the UK: Contexts, issues and prospects -- 15 Competence development and workplace learning: Enduring challenges in the interplay of policy and practice in the UK -- 16 Competence Domains and Vocational-Professional Education in Germany -- 17 The competence development agenda in France -- 18 Competence-based approach in the education reforms of Lithuania and Estonia -- 19 Competence-based Education in the Italian Context: State of Affairs and overcoming difficulties -- II.III Asian and African approaches -- 20 Competence-based education in China's higher TVET: The case of Shenzhen Polytechnic -- 21 Competence-based training in South Asia -- 22 Competence-based vocational education and training in Viet Nam: Input and process towards learning outcomes -- 23 Competence and TVET-Innovation in Sub-Saharan Africa; The case of Rwanda -- Part III Competence and Key Aspects of Education Systems -- III.I Generic Competence Frameworks for Education Systems -- 24 Competencies in Higher Education: Experience with the Academic Competencies and Quality Assurance (ACQA) Framework -- 25 Models and Principles for Designing Competence-based Curricula, Teaching, Learning and Assessment -- 26'4C your way': A competence framework for measuring competence growth from secondary vocational to higher education and curriculum design -- III.II Recognition, Assessment, Quality Management and Effectiveness -- 27 Comparing Recognition of Prior Learning (RPL) across countries -- 28 Competence assessment as learner support in education -- 29 Assuring quality in competence assessments: The value-added of applying different assessment approaches to professional education -- 30 Quality management of competence-based education -- 31 Competence-based education and educational effectiveness -- III.III Areas of Learning, Knowledge and Skills -- 32 Areas of Learning: The shift towards work and competence orientation within the school-based vocational education in the German Dual Apprenticeship System -- 33 Knowledge concepts in competence-based VET-research. Perspectives on cognitivist and social-constructivist approaches -- 34 Competence and the need for transferable skills -- III.IV Support for Teachers, Teaching and Learning -- 35 Factors influencing professional development in teacher teams within CBE contexts -- 36 Self-regulation and competence in formal and informal contexts of vocational and professional education -- 37 Fostering development of work competencies and motivation via Gamification -- 38 Software tools for scaffolding argumentation competence development -- Part IV Competence Domains -- IV.I Discipline-Oriented Competence Domains -- 39 Modeling, measurement and development of professional competencies in industrial-technical professions -- 40 Competence modelling and measurement in engineering mechanics -- 41 Modelling and Measurement of Teacher Competence: Old wine in new skins? -- 42 Competency-based Medical Education and its Competency-Frameworks -- IV.II Transversal Competence Domains -- 43 Green skills as the agenda for the competence-movement in TVET -- 44 Complex problem solving in a changing world: Bridging domain-specific and transversal competence demands in vocational education -- 45 Intuition as crucial component of professional competence: Its relevance for competence-based Vocational and Professional Education and Training -- 46 Labour market uncertainty and career perspectives: Competence in entrepreneurship courses -- 47 Becoming globally competent through student mobility -- 48 Social competence research: A review -- 49 Computational thinking as an emerging competence domain -- Conclusions and Discussion -- 50 Competence Theory and Research: A Synthesis.
Keywords: Education; Higher education; Lifelong learning